The Louisiana state constitution - Hargrave, W. Lee (Oxford commentaries on the state constitutions of the United States., 2011)
In The Louisiana State Constitution, Lee Hargrave provides a compehensive history and provision-by-provision commentary of the state's current constitution. Descriptive analysis provides readers with important information about the origins of the constitutional provisions, as well as ways in which the courts and other governmental bodies have interpreted them. Previously published by Greenwood, this title has been brought back in to circulation by Oxford University Press with new verve. Re-printed with standardization of content organization in order to facilitate research across the series, t.